E2E performance and fault analytic of VoIP on HSBB network / Khairul Hidayat M.Yusof - M.Yusof, Khairul Hidayat
Voice over IP (VoIP) are offer wide range of benefit. There is include reduction telecom costs, simplify the provisioning of service, wide range as long as have internet access, and ability to deploy new converged application. All provider pursuing the benefits of VoIP must take steps to ensure that their converged network delivers acceptable call quality and non-stop availability. In this paper, we investigate information regarding data integrity, service VoIP performance and fault management in the TM High Speed Broad-Band (HSBB) Network. Multi-vendor and multi technology environment is one of the big challenges for TM to identify, detect or pointed the faulty area. In this study, the main point is generating method on how to calculate performance for VoIP in entire HSBB network. Discuss the key point index (KPI) measurement for analyzed and identify to ensure network in the good condition. Also discuss in how End-to-End (E2E) network monitoring can play an important role in daily monitoring and troubleshooting network fault. The performance of the network is analyzed with active path, routing and traffic flow using measurement of throughput, packet loss, jitter delay, bandwidth and VoIP mean Opinion Score (MOS). From VoIP service, customer may experience on delay voice, choppy, echo, robotic sound, and call drop due to network physical error or packet loss. In this study, the method to probing network by active and passive probe will solve and help to manage performance and fault of the VoIP service. Each conversation using VoIP will rated with MOS value which is has 5 categories, bad, poor, fair, good and excellent. From this value, network engineer ease to analyzed QoS of the call and will process the proactive maintenance to solve QoS issue.